Patterns of Bidirectional Communication between Cortex and Basal Ganglia during Movement in Patients with Parkinson Disease - Lalo, Elodie (J Neurosci, 2008)
Cortico-basal ganglia networks are considered to comprise several parallel and mostly segregated loops, where segregation is achieved in space through topographic connectivity. Recently, it has been suggested that functional segregation may also be achieved in the frequency domain, by selective coupling of related activities at different frequencies. So far, however, any coupling across frequency in the human has only been modeled in terms of unidirectional influences, a misplaced assumption given the looped architecture of the basal ganglia, and has been considered in static terms. Here, we investigate the pattern of bidirectional coupling between mesial and lateral cortical areas and the subthalamic nucleus (STN) at rest and during movement, with and without pharmacological dopaminergic input, in patients with Parkinson's disease. We simultaneously recorded scalp electroencephalographic activity and local field potentials from depth electrodes and deduced patterns of directed coherence between cortical and STN levels across three frequency bands [sub-β (3–13 Hz), β (14–35 Hz), γ (65–90 Hz)] in the different states. Our results show (1) asymmetric bidirectional coupling between STN and both mesial and lateral cortical areas with greater drives from cortex to STN at frequencies <35 Hz, (2) a drop of β band coupling driven from mesial cortex to STN during movement, and (3) an increase in symmetrical bidirectional drives between STN and mesial cortex and in lateral cortical drive to STN in the γ band after dopaminergic therapy. The results confirm a bidirectional pattern of cortico-basal ganglia communication that is differentially patterned across frequency bands and changes with movement and dopaminergic input.